1961
DOI: 10.1042/bj0810028
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of griseofulvin: the methylated benzophenone intermediates

Abstract: for preparation of lignified coleoptiles and the suggestion that larger quantities of eugenol lignin could be produced on potato parenchyma. He is grateful to Mrs M. Szilagyi for technical assistance. The microanalyses were carried out by the Australian Microanalytical Service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0
1

Year Published

1962
1962
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 8 publications
(13 reference statements)
5
29
0
1
Order By: Relevance
“…However, formation of the latter could not be induced by using P. patulum (7), illustrating that such manipulations were strain or species dependent.…”
mentioning
confidence: 99%
“…However, formation of the latter could not be induced by using P. patulum (7), illustrating that such manipulations were strain or species dependent.…”
mentioning
confidence: 99%
“…overnight, discarding the aqueous layer and adding acetic acid (0.5% by vol.) to the upper layer (Rhodes, Boothroyd, McGonagle & Somerfield, 1961). System (XI) was modified from Coulson & Evans (1958) and was composed of benzene + acetic acid + water (20 + 5 + 4, by vol.).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, deletion of the methyltransferase GsfC clarified that the second methylation takes place at 2' before formation of the grisan ring in agreement with previous feeding studies. 82 Deletion of the third methyltransferase encoding gene GsfD showed that C-7 chlorination takes place before methylation of O-4 since desmethyl-dehydrogriseofulvin (13) accumulated. C-7 chlorination was also demonstrated to take place prior to grisan ring formation since griseophenone B (12) accumulated in the GsfF knockout strain.…”
Section: Fungal Biosynthesis Of Griseofulvinmentioning
confidence: 99%